Effects of common haplotypes of the ileal sodium dependent bile acid transporter gene on the development of sporadic and familial colorectal cancer: A case control study - Friedrichs Nicolaus; Plassmann Dominik; Schulte-Witte Hildegard; Becker Ursula; Keppeler Hildegard; Lamberti Christoph; Jungck Matthias; Grünhage Frank; Buettner Reinhard; Aretz Stefan; Sauerbruch Tilman; Lammert Frank (BMC, 2008)
Abstract Background The genetics of sporadic and non-syndromic familial colorectal cancer (CRC) is not well defined. However, genetic factors that promote the development of precursor lesions, i.e. adenomas, might also predispose to CRC. Recently, an association of colorectal adenoma with two variants (c.507C>T;p.L169L and c.511G>T;p.A171S) of the ileal sodium dependent bile acid transporter gene (SLC10A2) has been reported. Here, we reconstructed haplotypes of the SLC10A2 gene locus and tested for association with non-syndromic familial and sporadic CRC compared to 'hyper-normal' controls who displayed no colorectal polyps on screening colonoscopy. Methods We included 150 patients with sporadic CRC, 93 patients with familial CRC but exclusion of familial adenomatous polyposis and Lynch's syndrome, and 204 'hyper-normal' controls. Haplotype-tagging SLC10A2 gene variants were identified in the Hapmap database and genotyped using PCR-based 5' exonuclease assays with fluorescent dye-labelled probes. Haplotypes were reconstructed using the PHASE algorithm. Association testing was performed with both SNPs and reconstructed haplotypes. Results Minor allele frequencies of all SLC10A2 polymorphisms are within previously reported ranges, and no deviations from Hardy-Weinberg equilibrium are observed. However, we found no association with any of the SLC10A2 haplotypes with sporadic or familial CRC in our samples (all P values > 0.05). Conclusion Common variants of the SLC10A2 gene are not associated with sporadic or familial CRC. Hence, albeit this gene might be associated with early stages of colorectal neoplasia, it appears not to represent a major risk factor for progression to CRC.